Brn-3.0: a POU-domain protein expressed in the sensory, immune, and endocrine systems that functions on elements distinct from known octamer motifs. - Gerrero, M R (1993)
Characterization of Brn-3.0 and identification of a highly related member (Brn-3.1) of the class IV POU-domain family suggest potential roles of Brn-3.0 in the development of retinal ganglion cells and sensory neurons, as well as potential roles in the pituitary gland and the immune system. Brn-3.0 is expressed in the pituitary gland and in a corticotroph cell line. A functional DNA response element has been identified in the proopiomelanocortin promoter. In contrast to previously described mammalian POU-domain proteins, Brn-3.0 binds relatively ineffectively to known octamer DNA motifs, but instead binds with high affinity to a distinct set of DNA elements, functioning as a transcriptional activator. Brn-3.0, Brn-3.1, and the Drosophila tI-POU share an N-terminal region of homology, referred to as the "POU-IV box," which is similar to a conserved functional domain in the c-myc gene family.